Upaya Meningkatkan Karakter Mandiri Siswa TK B Puspa Melati Jember melalui Media Permainan Rakyat Engklek - Lutfiatul Munawaroh; Arifin Nur Budiono; Fakhruddin Mutakin (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
Character education is an effort to educate children in order to make decisions and practice them in their daily lives. Researchers are observing at TK B Puspa Melati Jember Odd semester year lesson 2019-2020 and obtained data about 46% or nearly half of the existing learners experiencing a level of low self-reliance. This research aims to improve the character's self-reliant through the game people's crank. The type of research used is research into class action (PTK). The procedure used is a cycle model. Based on the research results, the I cycle of students still has no independent attitude. Cycle II students have developed as expected (BSH), there are even some that are developing very well (BSB). It can be concluded that the people's games can improve the students ' independent character. Keywords: Independent Characters, the People's Game Crank